Probing the quantum–classical connection with open quantum dots. (7th October 2015) - Ferry, D K; Akis, R; Brunner, R
Abstract: Open quantum dots provide a natural system in which to study both classical and quantum features of transport. From the classical point of view these dots possess a mixed phase space which yields families of closed, regular orbits as well as an expansive sea of chaos. As a closed test bed, they provide a natural system with a very rich set of eigen-states. When coupled to the environment through a pair of quantum point contacts, each of which passes several modes, the original quantum environment evolves into a set of decoherent and coherent states, which eventually couple to the classical states discussed above. The manner of this connection is governed strongly by decoherence theory. The remaining coherent states possess all the properties of pointer states. Here, we discuss the quantum–classical connection and how it appears within the experimental world.